Accounting prototypes supporting product development: integrating different actors’ viewpoints - Rantamaa, Asta; Laine, Teemu; Korhonen, Tuomas (Proceedings of Pragmatic Constructivism, 2015)
This article introduces accounting prototypes in supporting managers in product development (PD), and inquires how accounting prototypes can support managers in PD activities. Accounting prototypes are jointly and iteratively created, preliminary tools, e.g., spreadsheets or information systems under development. Besides serving as control mechanisms, accounting prototypes also provide support for managers by integrating knowledge relevant to PD managers taking part in projects from different actors’ viewpoints. However, previous literature offers insufficient understanding of how accounting prototypes could help PD managers. The paper is based on an interventionist case study of a machinery manufacturer’s PD management. The focus of the case study was on the design and early use of accounting prototypes that would, right after PD execution, support production ramp-up, which was previously not much supported by accounting information. The paper contributes to the literature by showing an empirical example of supporting PD with accounting prototypes, and unveils the mechanisms through which the viewpoints of different business functions may be iteratively integrated in a calculation, thus enabling a more comprehensive view on the business impacts of a PD project. However, it was found out that the process of establishing and enhancing knowledge integration in the PD context is a longitudinal and challenging task also with the help of accounting prototypes.